Class Calcarea Bowerbank, 1864. Pp. 1103-1110. In: Hooper, J.N.A. & Van Soest, R.W.M. (eds). Systema Porifera - A guide to the classification of sponges - Manuel, M.; Borojevic, R.; Boury-Esnault, N.; Vacelet, J. (2002)
Calcarea Bowerbank (Porifera) includes sponges having a mineral skeleton composed entirely of calcium carbonate, consisting of free, rarely linked or cemented, di-, tri-, tetra- and/or polyactinal spicules, sometimes with a solid basal calcitic skeleton, and with blastula larvae and viviparous mode of reproduction. Two Recent subclasses are recognised, Calcinea and Calcaronea, containing five orders, 22 families and 75 valid genera, with species exclusively marine and distributed worldwide.